INSIGHT INTO THE IMPLEMENTATION OF THE IFS FOOD VERSION 8 REQUIREMENTS IN THE FOOD SAFETY MANAGEMENT SYSTEM: KEY STEPS AND BENEFITS - MARIANA-LILIANA PĂCALĂ; CIPRIAN CĂPĂȚÂNĂ; SIMONA OANCEA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Food safety is essential throughout the entire food chain. An efficient Food Safety Management System (FSMS) establishes a robust foundation for ensuring food safety by identifying and reducing risks, enhancing operational efficiency, and supporting the continuous adaptation to emerging hazards and control methods. This research focused on the implementation and updating of the FSMS in accordance with the requirements of the latest version of the IFS (International Featured Standards) Food standard, version 8 (v8), an internationally recognized standard for food safety, quality, and compliance in the supply chain. The study employed the action research method, combining the theoretical analysis of specialized literature with practical application in a food company, with the aim of facilitating the implementation process by identification of the key steps for the successful implementation of IFS Food v8 requirements. A case study is presented that analyzes the evolution of the FSMS in a food company, starting with the implementation of a Quality Management System (QMS) compliant with the ISO 9001:2000 standard. This system was gradually adapted and improved in line with changes in food safety standards, ultimately achieving certification in accordance with the requirements of IFS Food v8. Addressing relevant aspects has enabled us to highlight and classify the principal benefits of this implementation. This study contributes to the documentation aimed at enriching perspective and addressing multidisciplinary challenges in the field of FSMS. Also, it provides valuable insights for companies interested in implementing the IFS Food v8 standard, and easier access to emerging business opportunities in the food market.